A systemic sociological theorem of global evolution - Andrea Pitasi (Revista de Direito Econômico e Socioambiental, 2013)
Starting from an interdisciplinary perspective this essay is focalized on the analysis regarding how the megatrends of demography, technological convergence and world order redesign are shaping a dematerialized global scenario in which a key bifurcation is emerging: on one side the Malthus Trap on the other one the Gegnet, the limitless opening of the possible. The abstraction level of the big data turn into meaningless each local based empirical research that is why the key epistemological challenge of this essay is to evolve the systemic paradigm comprehend big data and the methodological challenge is to draft a deductive nevertheless big data based, theorem of global evolution.